2019
DOI: 10.20960/nh.02352
|View full text |Cite
|
Sign up to set email alerts
|

Feeding patterns and growth trajectories in breast-fed and formula-fed infants during the introduction of complementary food

Abstract: Objetivo: el objetivo de este estudio fue evaluar la prevalencia de hipovitaminosis D en los candidatos a cirugía bariátrica (CB) y su relación con factores de riesgo y los componentes del síndrome metabólico. Material y métodos: los parámetros clínicos, antropométricos y bioquímicos se midieron en 56 pacientes caucásicos incluidos en un protocolo de cirugía bariátrica entre enero y junio de 2014. Los pacientes fueron estratificados en tres grupos de acuerdo al status de vitamina D: suficiencia (≥ 40 ng/ml), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 0 publications
0
20
0
4
Order By: Relevance
“…Notably, we also found that parental allergy history and gender were closely associated with intensity of DF/ HDM allergens, F-M and boys group showed the highest intensity, which indicated that more attention should be paid to this group in the prevention of asthma/ALS. Finally, we observed that age was negatively associated with the positive rate of food allergens before the infection point of 3.42 years of age, whereas age was not associated with the positive rate of food allergens after the infection point of 3.42 years of age, which may be explained by the facts that food patterns changes a lot during the infantile period, leading to a higher positive rate of food allergens before this period [16]. Meanwhile the food patterns were comparatively stable after infantile period.…”
Section: Discusssionmentioning
confidence: 62%
“…Notably, we also found that parental allergy history and gender were closely associated with intensity of DF/ HDM allergens, F-M and boys group showed the highest intensity, which indicated that more attention should be paid to this group in the prevention of asthma/ALS. Finally, we observed that age was negatively associated with the positive rate of food allergens before the infection point of 3.42 years of age, whereas age was not associated with the positive rate of food allergens after the infection point of 3.42 years of age, which may be explained by the facts that food patterns changes a lot during the infantile period, leading to a higher positive rate of food allergens before this period [16]. Meanwhile the food patterns were comparatively stable after infantile period.…”
Section: Discusssionmentioning
confidence: 62%
“…Although we focused on energy intake from complementary foods at 10.5 months only, energy intake from the complementary was higher in FF compared to BF infants. Research has shown that FF infants are introduced to complementary foods at an earlier age, 48 and their total food 49 and energy intake from formula and complementary foods 42 is greater in the first year when compared to BF infants.…”
Section: Discussionmentioning
confidence: 99%
“…В других исследованиях было показано, что раннее приучение младенцев к овощам и фруктам предупреждает развитие отсроченной сердечно-сосудистой патологии [24]. Предполагается, что профилактические свойства этих продуктов связаны с более низкой по сравнению с зерновыми прикормами гликемической нагрузкой, антиоксидантными свойствами и наличием клетчатки.…”
Section: раннее пищевое программирование и особенности введения блюдunclassified